Species in the Cryptococcus gattii Complex Differ in Capsule and Cell Size following Growth under Capsule-Inducing Conditions - Kenya E. Fernandes (American Society for Microbiology, 2016)
ABSTRACT Cryptococcus gattii causes invasive fungal infections that have been increasing in incidence and global distribution in recent years. The major molecular genotypes of C. gattii that were previously classified as VGI to VGIV have recently been described as four new species: C. gattii (VGI), C. deuterogattii (VGII), C. bacillisporus (VGIII), and C. tetragattii (VGIV). The main driver for their classification has been phylogeny, and phenotypic diversity has not yet been extensively characterized. This study examines variation in attributes related to virulence and pathogenicity, including capsule thickness, cell size, tolerance to temperature, oxidative and osmotic stress, and cell wall integrity. A capsule induction agar using diluted Sabouraud medium revealed significant differences in capsule and cell size across the C. gattii species complex and produced irregularly shaped elongated cells in a number of strains. C. gattii/VGI strains possessed the largest capsules of all species but had smaller cells, while C. deuterogattii/VGII strains possessed the largest cells of all species but had smaller capsules. Overall thermotolerance was highest in C. deuterogattii/VGII strains, while a number of C. bacillisporus/VGIII, and C. tetragattii/VGIV strains had substantially reduced growth at 37°C. There was no significant difference among species in their tolerances to oxidative or osmotic stresses, and there was no evidence for defects in cell wall integrity in strains producing irregular cells. These data support the division of the C. gattii species complex into distinctly identified species and suggest underlying reasons for their differences in virulence, epidemiology, and host preference. IMPORTANCE Infections with the fungal pathogen Cryptococcus gattii have been increasing in recent years. Recently, four different species have been described within C. gattii, which correspond to four previously known molecular genotypes (VGI to VGIV). Examining traits related to infection and disease is important for determining whether these different species have clinical relevance. This study examined variation in attributes that are important for infecting and surviving in the host, including tolerance to various stresses, yeast cell size, and the amount of polysaccharide capsule that covers the cell. The cell size and capsule size were significantly different and inversely correlated across the species. Thermotolerance was highest in C. deuterogattii (VGII), the only species known to cause outbreaks, while most strains of the species C. bacillisporus (VGIII) and C. tetragattii (VGIV) grew poorly at 37°C. These findings argue for increased acceptance of the new species and may be useful for informing diagnosis and prognosis in clinical infection.